Who feels academically efficacious? Moving beyond the gender binary - Martin, Carol Lynn; Xiao, Sonya Xinyue; Peng, Anqi; Hanish, Laura (Frontiers in Developmental Psychology, 2025)
The goal was to explore global and domain-specific academic motivation using fine-grained assessments of self-social gender identity, specifically, early adolescent students' ratings of “gender similarity,” that is, how similar they feel to the two major gender collectives. From these assessments, four profiles of gender identity were generated and were used to explore how variations in profiles related to both general and specific academic motivation. Participants included an ethnically/racially diverse community sample of binary-identified children (n = 1,642; 47% girls; Mage = 9.05, SD = 0.91) in Grades 3 to 5 from 77 classrooms in eight elementary schools. Analyses revealed that global motivation was significantly higher for students who reported feeling similar to one or both gender collectives, and lowest for those who reported low feelings of similarity to both gender collectives. Specific motivation in gender-specific domains showed a different pattern: students who feel similar to the gender expected to succeed in the academic domain did not show higher motivation in those gender-stereotyped academic domains. The findings suggest that the self-social gender identity is important for understanding global academic motivation but less so for understanding academic motivation in specific gender-stereotypic domains such as reading and math/science.